Improving Students Critical Thinking Skills and Sustainability Awareness using Problem Based Learning Model - Maulina*, Dina; Priadi, Median Agus; Gustina, Melin; Rakhmawati, Ismi (Universitas Syiah Kuala, 2025)
This research aims to determine the increase in students' critical thinking skills (CTS) and sustainability awareness in SDGs issue-oriented climate change material using a problem-based learning (PBL) model. This type of research is quantitative research, the research design is quasi-experimental with a pretest-posttest non-equivalent control group design technique. The research sample consisted of two classes selected using purposive sampling technique. Research data was obtained by providing a pretest and posttest to determine the increase in CTS and an observation sheet to determine students' sustainability awareness data. The pretest-posttest scores in the experimental class using the PBL model obtained an average N-gain score of 0.52, including the medium category. The effect size test also obtained a value of 2.88 with the